Analysis Income, Expenditure, Financing, and Realization Reception Tax Land and Buildings in the Regency South Konawe 2019–2023 - Asrip Putera; Eliyanti Agus Mokodompit; Andriani Puspitaningsih; Isalman (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: This article analyzes the fiscal performance of the South Konawe Regency government during the 2019–2023 period, with a focus on regional income, expenditures, financing, and Land and Building Tax revenue. Objective:The objective is to evaluate the fiscal stability of the region, identify potential improvements in income generation, and review the financing strategies implemented by the local government. Method:This study is based on an analysis of secondary data obtained from the South Konawe Regency’s annual financial reports, which include data on income, expenditures, financing, and revenue. Results:The analysis reveals significant fluctuations in regional income and expenditures, with fiscal imbalances observed in 2019 and 2023. The region's reliance on surplus financing from the previous year (SiLPA) indicates a need to reduce dependency on such financing. Additionally, the mining sector's contribution to regional income shows suboptimal potential. The fiscal performance evaluation suggests that the region’s fiscal management requires optimization, particularly by increasing local original revenue and managing natural resource sectors in a sustainable manner. Conclusion:The local government needs to formulate more effective and efficient fiscal policies to support sustainable regional development. Keywords: fiscal performance; regional income; financing; Land and Building Tax; South Konawe; natural resources; fiscal analysis